Optic Nerve Angle in Idiopathic Intracranial Hypertension. Issue 4 (December 2021) - Chen, Benson S.; Asnafi, Solmaz; Lin, Mung Y.; Bruce, Beau B.; Lock, Jane H.; Sharma, Rahul A.; Newman, Nancy J.; Biousse, Valérie; Saindane, Amit M.
Abstract : Background: The tortuosity of the optic nerve can be quantified radiologically by measuring the angle of optic nerve deformation (the "optic nerve angle" [ONA]). In patients with idiopathic intracranial hypertension (IIH), lowering the intracranial pressure (ICP) to a normal range by lumbar puncture leads to straightening of the optic nerve and an increase in the measured sagittal ONA on MRI. It is uncertain whether there is any correlation between ONA and cerebrospinal fluid (CSF) opening pressure or visual function. Methods: Retrospective study of patients with and without IIH who had MRI of the brain followed by lumbar puncture with CSF opening pressure within 24 hours of MRI. Before LP and within 24 hours of MRI of the brain, all patients with IIH had neuro-ophthalmologic assessment including visual acuity, Humphrey Visual Field (HVF), and fundus photography. Sagittal ONA was measured on multiplanar T2-SPACE images on a DICOM viewer. Papilledema on the fundus photographs was graded using the Frisén scale. Results: Fifty-four patients with IIH and 30 unmatched controls were included. The IIH group was 6.3 years younger (95% CI 2.4–10.3, P = 0.002), had 8.7 kg/m 2 higher body mass index (4.9–12.5, P < 0.001), and 26.3% more women ( P = 0.011) compared with controls. In both eyes, the ONA was significantly smaller in patients with IIH by 12° compared with controls (7°–17°, P < 0.00001). In the IIH group, no correlation between ONA and the CSF opening pressure was present in either eye (right eye r = 0.19, P = 0.15; left eye r = 0.18, P = 0.19) The ONA did not correlate with logarithm of the minimum angle of resolution visual acuity (right eye r = 0.26, P = 0.063; left eye r = 0.15, P = 0.27), HVF mean deviation (right eye r = 0.0059, P = 0.97; left eye r = −0.069, P = 0.63), or Frisén grade (Spearman's rho right eye 0.058, P = 0.67; left eye 0.14, P = 0.30). Conclusions: The ONA is significantly smaller in patients with IIH compared to controls, but does not correlate with CSF opening pressure, severity of papilledema, or visual function. The ONA may be useful in identifying patients with raised ICP, but not necessarily those with a poor visual prognosis.